Autonomous Drift Parking using a Switched Control Strategy with Onboard Sensors. Issue 1 (July 2017) - Jelavic, E.; Gonzales, J.; Borrelli, F.
Abstract: Drift parking represents an extreme maneuver that is beyond the skill set of the average driver, requiring adept use and timing of the handbrake, pedal brake, and steering wheel. The maneuver causes the vehicle to rotate rapidly and slide, nearly sideways (i.e. high side slip angle), into the desired parking spot. In this paper we propose a control strategy to quickly park a vehicle in a narrow space using a high side slip angle maneuver, or 'drift parking' maneuver. The proposed control scheme switches between nonlinear model predictive control and a linear feedforward-feedback policy. For experimental validation, we use an open source, low cost 1/10 scale RC vehicle called the Berkeley Autonomous Race Car developed at UC Berkeley.